V.1 - Subramanian, S.; Mishra, Ranganath(fwd.) (New Delhi, 2004)
The book covers exhaustively the Historical Perspective; Human Rights and Social Development; Rights of the Child, Women, Workers and the Juveniles; Human Rights in Criminal Justice System; Implementation Procedures and Enforcement of Human Rights; National Human Rights Commission; the NGOS; Human Rights Situation in the neighbouring countries and in India and Human Rights Awareness.
Keywords: Human rights-india